Integrative analyses of prognosis, tumor immunity, and ceRNA network of the ferroptosis-associated gene FANCD2 in hepatocellular carcinoma - Yang, Zhihao; Song, Yaoshu; Li, Ya; Mao, Yiming; Du, Guobo; Tan, Bangxian; Zhang, Hongpan (Frontiers in Genetics, 2022)
Extensive evidence has unwrapped that ferroptosis exerts a vital role in HCC development and progression. Fanconi anemia complementation group D2 (FANCD2) has reported to serve as a ferroptosis-associated gene and has close relation with tumorigenesis and drug resistance. However, the impact of FANCD2-related immune response and mechanisms on HCC remains incompletely transparent. In the current research, we evaluated the prognostic significance and immune-associated mechanism of FANCD2 based on multiple bioinformatics methods and databases. The results demonstrated that FANCD2 was commonly upregulated in 15/33 tumors, and only the high expression of FANCD2 in HCC was closely correlated with worse clinical outcomes through OS, and DFS analysis. Moreover, ncRNAs, including two major types: miRNAs and lncRNAs, were closely involved in mediating FANCD2 upregulation in HCC and were established to ceRNA network by performing various silico analyses. DUXAP8-miR-29c-FANCD2 and LINC00511-miR-29c-FANCD2 axis were identified the most possible ncRNA-associated upstream regulatory axis of FANCD2 in HCC. Finally, FANCD2 expression was confirmed to be positively related to HCC immune cell infiltration, immune checkpoint, and IPS analysis and GSEA enrichment results also revealed this ferroptosis-associated gene to be primarily involved in cancer-associated pathways in HCC. In conclusion, our investigations indicate that ncRNAs-related modulatory overexpression of FANCD2 might act as a promising prognostic and immunotherapeutic target against HCC.